Oxytocin and the role of "regulator of emotions": Definition, neurobiochemical and clinical contexts, practical applications and contraindications - Giulio Perrotta (Archives of Depression and Anxiety - Peertechz Publications, 2020)
In the field of neuroscience applied to emotions and affects, some hormones have been studied for their relational and social activation capacity. Among these, the peptide hormone called oxytocin, long known for the induction of birth contractions and other physiological functions, is involved in attachment, confidence and reduction of anxiety, facilitating the stability of emotional relationships and therefore loyalty and love. Therapeutic uses are then proposed for synthetic oxytocin for eating disorders, substance addictions and even autism. In the following review, the primary experimental evidence and the possible side effects are proposed again, orienting the study on more detailed specific investigations.